The Constitution in Cyberspace. - Tribe, Laurence H. (Humanist)
Argues that in a world reconstituted by the microchip, the U.S. Constitution may come to seem quaintly irrelevant. Case of Maryland vs. Craig, which allows accuser to testify by one-way closed-circuit television; Applicability of the First Amendment to cyberspace; Five basic Constitutional assumptions and how they can be adapted to the cyberspace age; Conclusion.